2016
DOI: 10.1093/eurheartj/ehw156
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the oxygen sensor prolyl hydroxylase 1 attenuates hypercholesterolaemia, atherosclerosis, and hyperglycaemia

Abstract: Overall, PHD1 knockout mice display a metabolic phenotype that generally is deemed protective for cardiovascular disease. Future studies should focus on the efficacy, safety, and gender-specific effects of PHD1 inhibition in humans, and unravel the molecular actors responsible for PHD1-driven, likely intestinal, and regulation of cholesterol metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 13 publications
1
39
0
2
Order By: Relevance
“…1), mice with systemic HIF-P4H-1 (PHD1/EglN2) deficiency lowered their skeletal muscle O2 consumption through activation of PPARα as well as HIF2α-mediated development of hypoxia tolerance [17] but had no difference in body weight [18]. These mice also displayed reduced LDL-C levels, less circulating immune cells, and an improved glucose tolerance [9] (Fig. 4).…”
Section: Hypoxia Hifs and Hif-p4hs In Obesity Metabolic Syndrome Anmentioning
confidence: 97%
See 1 more Smart Citation
“…1), mice with systemic HIF-P4H-1 (PHD1/EglN2) deficiency lowered their skeletal muscle O2 consumption through activation of PPARα as well as HIF2α-mediated development of hypoxia tolerance [17] but had no difference in body weight [18]. These mice also displayed reduced LDL-C levels, less circulating immune cells, and an improved glucose tolerance [9] (Fig. 4).…”
Section: Hypoxia Hifs and Hif-p4hs In Obesity Metabolic Syndrome Anmentioning
confidence: 97%
“…Since HIFs regulate many processes beyond erythropoiesis ( Fig. 1), HIF-P4H inhibition has been exploited widely in preclinical conditions, and indeed found beneficial in ischemic and inflammatory conditions (for reviews see [3,4]) and lately in metabolic diseases [4][5][6][7][8][9]. However, there exists concern about the use of HIF-P4H inhibitors.…”
Section: Hif-p4h Inhibitors and Renal Anemia -What About Beyond?mentioning
confidence: 99%
“…The first-in-class small-molecule HIF-P4H inhibitor that activates the hypoxia response has been approved for treatment of renal anemia and several others are in clinical trials [10,11]. Recent data suggest that besides anemia, HIF-P4H inhibition and hypoxia are powerful tools for promoting metabolic health [10,[12][13][14][15][16][17]. We have previously shown that genetic HIF-P4H-2 deficiency protects the Hif-p4h-2 gt/gt mice against metabolic disorder-related hepatic steatosis and chemically induced HCC [14,18], and against alcoholic liver disease (ALD) by downregulating hepatic lipogenesis and improving the elimination of harmful ethanol metabolites and reactive oxygen species [19].…”
Section: Introductionmentioning
confidence: 99%
“…PHD1 deficiency has recently been linked to lowered serum cholesterol levels, resistance to hyperglycaemia and an impaired development of atherosclerotic plaques in mice (Marsch et al . ). Intriguingly, in a rat model of gestational hypertension, PHD1 was associated with a reduction in blood pressure after physical exercise (Gilbert et al .…”
Section: Molecular Oxygen Sensing In Metazoan Cellsmentioning
confidence: 97%